Proposal of an educational technology approach for a web system construction. Application case: teaching about the Fungi kingdom - Benito Moran, Daniel; Soberanes Martín, Anabelem (IE Revista de Investigación Educativa de la REDIECH, 2021)
Educational technology, as it is nowadays understood, is a relatively new concept. Traditionally, it was understood as the use of audiovisual materials in the classroom; however, this concept has been left behind to be considered a fundamental part of educational processes, taking into account multiple disciplines. This research links theoretical foundations with the development of a web system considering pedagogical aspects for the generation of educational technology; this is done in three stages: (1) seeking educational foundation and its adaptation to technology, (2) the applicability of these to the concept of usability and (3) the development of the system web. The results obtained were favorable; the SUS (Scale Usability System) tool determined a usability level of 91.38. In this sense, creating a system that managed information about the Fungi kingdom considers the incorporation of pedagogical and technological techniques during the elaboration process. Considering the characteristics of the end-user will help the teaching-learning process and, thus, keep the interest from the user to continue using the generated instrument.